Чисельна методика прогнозування твердості поверхневих шарів державки твердосплавного різця в результаті загартування після індукційного паяння - Дутка, В.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The numerical technique of prognostication of the hardness and thickness of surface layer of the hard alloy cutter holder in results of the hardening after induction soldering is presented. This technique is based on: 1) numerical modelling of temperature field in hard alloy cutter during hardening; 2) using of the thermokinetic diagram for phase transformations of austenite during cooling of steel holder. The results of prognostication of the hardness and thickness of surface layer of the steel (35ХГСА) holder in results of the hardening in water solution of salt and alkali at temperature 300, 200 and 100 ºС and in machine oils at 20 ºС are presented. It is shown that in results of the hardening in water solution of salt and alkali the highest hardness of surface layer can be to obtain, but in results of the hardening in machine oils can’t be to obtain the highest hardness of surface layer of steel holder.